2023
DOI: 10.3390/nano13020255
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biomaterials Based on Biomimetic Trace Elements Co-Doped Hydroxyapatite: Physical, In Vitro Osteoblast-like Cell Growth and In Vivo Cytotoxicity in Zebrafish Studies

Abstract: Synthesized hydroxyapatite (sHA)—calcium phosphate (CaP) based biomaterials play a vital role and have been widely used in the process of bone regeneration for bone defect repair, due to their similarities to the inorganic components of human bones. However, for bone tissue engineering purpose, the composite components, physical and biological properties, efficacy and safety of sHA still need further improvements. In this work, we synthesized inhomogeneous hydroxyapatite based on biomimetic trace elements (Mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Furthermore, in vivo tests demonstrated that the magnetic HA particles were non-toxic and did not have any adverse effects on embryonic zebrafish. With these promising physical and biological properties, synthesized material has been reported as a possible biomaterial candidate for bone tissue applications [ 170 ].…”
Section: Methods Of Magnetic Hydroxyapatite Synthesismentioning
confidence: 99%
“…Furthermore, in vivo tests demonstrated that the magnetic HA particles were non-toxic and did not have any adverse effects on embryonic zebrafish. With these promising physical and biological properties, synthesized material has been reported as a possible biomaterial candidate for bone tissue applications [ 170 ].…”
Section: Methods Of Magnetic Hydroxyapatite Synthesismentioning
confidence: 99%
“…These quality control assays should indicate whether the produced dressings are biomimetic, bioadhesive, and biointegrated and whether they support epithelial tissue growth and maturation. Hence, studying these measurements to find answers to these questions is not without grace ( Tithito et al, 2023 ). H&E staining is used as one of the common techniques to determine the effectiveness of skin dressings.…”
Section: Biomaterial-based Wound Dressing Quality Controlsmentioning
confidence: 99%
“…The hydroxyapatite (HA, Ca 10 (PO 4 ) 6 (OH) 2 ) is the main inorganic constituent of bone tissue. Synthetic HA has been successfully used to fabricate biomaterials, osteogenic coatings, and other materials of biomedical interest [1][2][3][4][5]. There are different methodologies for fabrication of calcium phosphates, such as solid-state syntheses [6][7][8][9], hydrothermal syntheses [10][11][12][13][14][15], biomimetic systems [16][17][18], electrochemical process [19][20][21], and sol-gel methods [5,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%